2013
DOI: 10.1182/blood.v122.21.2952.2952
|View full text |Cite
|
Sign up to set email alerts
|

Survey Of Patients Referred To a University Cancer Center For Benign Hematology: Quality Measures and Patient Understanding

Abstract: Background Traditionally, benign blood disorders are being evaluated and managed by hematologists who are also trained in oncology. Many of these physicians have their clinics located in Cancer Centers. Based on our clinical observations, the term “Cancer Center” is misleading to many benign hematology patients and it may affect their perception of their disease and/or reason for referral. There are currently no studies investigating patient understanding of benign hematology, the impact of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 0 publications
0
9
1
Order By: Relevance
“…A previous study that investigated patients' knowledge and understanding of nonmalignant blood disorders found that patients may not fully understood the signi cance of such conditions. 31 In contrast, almost all patients in our study seemed to understand key aspect of MGUS, although a few patients recognized that they do not have a good understanding of the condition. We found that providers recognized that patients with MGUS could experience anxiety associated with MGUS diagnosis and longterm follow-up.…”
Section: Discussionmentioning
confidence: 56%
“…A previous study that investigated patients' knowledge and understanding of nonmalignant blood disorders found that patients may not fully understood the signi cance of such conditions. 31 In contrast, almost all patients in our study seemed to understand key aspect of MGUS, although a few patients recognized that they do not have a good understanding of the condition. We found that providers recognized that patients with MGUS could experience anxiety associated with MGUS diagnosis and longterm follow-up.…”
Section: Discussionmentioning
confidence: 56%
“…Patients may experience high distress after a diagnosis of premalignant MGUS. [35][36][37] This associated anxiety could result in a change (overutilization/underutilization) in healthcare utilization and clinical surveillance beyond what is necessary. 38 Quantifying the care and surveillance of patients with MGUS is of clinical relevance given that multiple myeloma patients with a pre-existing MGUS diagnosis have been shown to have a better multiple myeloma prognosis.…”
Section: The Impact Of a Diagnosis Of Mgus On Healthcare Utilizationmentioning
confidence: 99%
“…22,53,38 Despite the relatively low risk of progression, patients with a diagnosis of MGUS are generally followed up every 6-12 months for signs of progression to malignancy. [35][36][37] It is not currently possible to predict which patients with MGUS are more likely to progress to multiple myeloma. 54 Elevated monoclonal (M)-protein concentration, 38 immunoglobulin M or A isotype, 38 abnormal bone marrow plasma cells 55,56 and abnormal free light chain ratios are risk factors for progression of MGUS to multiple myeloma.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with MGUS progress to MM at a rate of approximately 1% annually 15‐17 . Despite the relatively low risk of progression, patients with a diagnosis of MGUS are generally followed with testing every 6–12 months for signs of progression to malignancy 18‐20 …”
Section: Introductionmentioning
confidence: 99%